Pengaruh Kepatuhan Pengendalian Internal terhadap Perilaku Etis Karyawan dalam Sistem Penggajian : (Studi kasus pada karyawan KSP Kopdit Tuke Jung) - Marlina Kristanti; Henrikus Herdi; Wihelmina Maryetha Yulia Jaeng (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
This study aimed to examine the effect of internal control compliance on employee ethical behavior within the payroll system at KSP Kopdit Tuke Jung. The research utilized an associative approach with a causal relationship and employed a quantitative method. The population and sample consisted of all employees at KSP Kopdit Tuke Jung, totaling 62 respondents. Data analysis was performed using multiple linear regression with the Statistical Package for the Social Sciences (SPSS). The findings revealed that partially: (1) Control environment did not have a significant effect on employee ethical behavior within the payroll system, (2) Risk assessment did not significantly impact employee ethical behavior within the payroll system, (3) Control activities had a significant effect on employee ethical behavior within the payroll system, (4) Information and communication did not significantly affect employee ethical behavior within the payroll system, and (5) Monitoring had a significant effect on employee ethical behavior within the payroll system. Simultaneously, the independent variables collectively influenced the dependent variable.